Analisis Tingkat Kepuasan Masyarakat terhadap Sistem Pelayanan Pengangkutan Sampah di Jalan Berdikari, Kelurahan Padang Bulan, Kecamatan Medan Baru - Ginting, Dora Karyati Br; Rossevelt, Franklin Asido; Aisyah, Dara; Mariani, Dinda; Silitonga, Chelsea Rahmadhani; Lubis, Najwa Rahmadani (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to analyze the level of community satisfaction with the waste collection service on Berdikari Street, Padang Bulan Village, Medan Baru District, Medan City, and to examine the influence of service quality (SERVQUAL dimensions) on that satisfaction. The research uses a descriptive quantitative approach with a survey method. Data were collected via questionnaires from local residents, covering service quality indicators across five SERVQUAL dimensions (tangibles, reliability, responsiveness, assurance, and empathy). Data analysis was conducted by calculating a Community Satisfaction Index (CSI) and performing a Pearson correlation test to assess the relationship between service quality and satisfaction. The results show that the community’s satisfaction level falls into the “satisfied” category with a CSI value of around 78.5%. However, two service dimensions reliability and responsiveness scored lower than the others, indicating the need for improvements in collection schedule punctuality and speed of response to complaints. The statistical analysis confirms a significant positive relationship between service quality and community satisfaction. In conclusion, the better the perceived quality of the waste collection service, the higher the community’s satisfaction; thus, improvements in reliability and responsiveness are recommended to further enhance resident satisfaction.